PROSPECTS FOR THE USE OF ARTIFICIAL INTELLIGENCE IN THE TEACHING OF ARCHITECTURE AND DESIGN - Troshkin, Arsenii; Makukhin, Dmytro (Theory and practice of design, 2025)
This article explores the prospects of integrating Artificial Intelligence (AI) into the educational process within the fields of architecture and design. The relevance of the topic stems from the rapid increase in AI usage among students, which, on the one hand, opens new opportunities for modeling, visualization, and automation, and on the other – raises concerns about reduced independent thinking, homogenization of results, and reliance on templates. Purpose. The aim of the study is to justify the feasibility of integrating AI into the learning process while preserving creativity, fostering critical thinking, and updating pedagogical strategies. The authors seek to demonstrate that, with proper methodological guidance, AI can become an effective tool in project-based learning. The research methodology is based on the analysis and synthesis of educational cases, modeling of learning scenarios, comparative analysis of two typical models of AI use, and a SWOT analysis of their strengths and weaknesses. As a result, two representative models of AI usage in project-based activities are identified: an active model, involving generative tools at all stages of work (as in UX/UI design), and a limited model, in which AI is used minimally as a supporting tool (as in architectural design). The study analyzes the benefits and risks of each model in terms of analytical thinking development, authorship, and market relevance. The scientific novelty lies in the systematization of approaches to AI integration in the education of designers and architects, and in the proposed typology of models based on the level of AI autonomy in the design process. The practical relevance of the study lies in the development of methodological guidelines for educators that help maintain a balance between the innovative use of digital tools and the cultivation of students’ creative potential. The results can be adapted and used to develop updated curricula across various fields that require regulated and purposeful integration of AI. At the same time, the study emphasizes the need to develop pedagogical strategies that balance technological advancement with the development of individual thinking.